Globalisation and the spread of terrorism in northern and sub-Saharan Africa : causes and consequences : a thesis submitted in partial fulfilment of the requirements for the Master of Defence Studies at Massey University - Smith, Una (Massey University, 2011)
The problems of Africa have for so long seemingly been ignored or played down. Poverty, political corruption and the adverse effects of globalisation have taken their toll. This can lead people to a feeling of desperation which leads to a willingness to do anything to escape their fate. A surplus in failed states means an increase in terrorism, transnational crime, and piracy. This work explores the preconditions of terrorism to flourish, and the conditions that are prevalent in regions of Africa.
Keywords: Northern Africa; Sub-Saharan Africa; Terrorism; Political corruption, Africa; Globalisation, Africa; Economic conditions, Africa